PENGARUH KUALITAS LAYANAN, KOMPETENSI PEGAWAI DAN FASILITAS TERHADAP KEPUASAN MASYARAKAT DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA SEMARANG - Rafi Alfaritzi, Muhammad; Rahmaningtyas, Wisudani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of service quality, employee competence, and facilities on public satisfaction at the Department of Population and Civil Registration of Semarang City. This research employed a quantitative approach with an associative method. The sample consisted of 96 respondents selected through random sampling. Data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination using SPSS. The results showed that partially service quality had a positive and significant effect on public satisfaction with a regression coefficient of 0.437 and significance value of 0.000, employee competence had a positive and significant effect with a coefficient of 0.164 and significance value of 0.011, and facilities had a positive and significant effect with a coefficient of 0.293 and significance value of 0.000. Simultaneously, these variables significantly affected public satisfaction with an F-value of 41.924 and significance value of 0.000. The Adjusted R Square value of 0.564 indicates that 56.4% of the variation in public satisfaction is explained by the model. Service quality was found to be the most dominant variable affecting public satisfaction. These findings emphasize the importance of improving service quality, employee competence, and facilities to enhance public satisfaction in public services.